Effectiveness of the Implementation of Restorative Justice in the Juvenile Criminal Justice System - Henny Saida Flora; Harmono Harmono; Livia Alves (Rechtsnormen: Journal of Law, 2025)
Background. The juvenile criminal justice system has evolved to incorporate restorative justice (RJ) practices, which emphasize repairing harm and rehabilitating offenders through dialogue and reconciliation. The implementation of RJ in juvenile justice systems aims to provide an alternative to punitive measures and encourage offenders to take responsibility for their actions while addressing the needs of victims and communities. Despite its promise, the effectiveness of RJ in reducing recidivism and promoting positive outcomes for juvenile offenders remains underexplored. Objective. This study aims to evaluate the effectiveness of restorative justice practices in the juvenile criminal justice system, focusing on recidivism rates, victim satisfaction, and the rehabilitation of juvenile offenders. The research seeks to assess whether RJ methods contribute to better long-term outcomes compared to traditional punitive approaches. Method. A mixed-methods approach was employed, combining quantitative analysis of recidivism rates and qualitative interviews with juvenile offenders, victims, and justice system professionals involved in RJ programs. Results. The findings show that restorative justice significantly reduces recidivism rates and improves victim satisfaction. Juvenile offenders reported feeling more accountable for their actions, and communities experienced a greater sense of justice and restoration. Conclusion. Restorative justice practices prove to be effective in the juvenile criminal justice system, offering promising alternatives to traditional punitive methods. Policymakers should consider expanding RJ programs to further enhance rehabilitation and community healing.